Pengetahuan, sikap, kepercayaan, dan perilaku budaya tradisional generasi muda di Ambon - Widiyanto, T. Sigit; Gurning, Elizabeth T. (Jakarta : Departemen Pendidikan dan Kebudayaan, 1997)
Cultural attitudes of youth against customs and traditions in Ambon, Maluku Province; research report.
Keywords: Youth -- Indonesia -- Ambon -- Attitudes; Public opinion -- Indonesia -- Ambon; Ambon (Indonesia) -- Social life and customs -- Public opinion